(untitled) (Scientific journal of the Fergana State University, 2024)
Studies of ichthyofauna of ditch waters of Rishton district were carried out for the first time. This article provides information on the current species composition of the ichthyofauna of the ditches of Rishton district. 8 species of fish have been found in the ditches of Rishton district. 4 fish species are local and endemic species, with Pseudorasbora parva Schizothorax eurystomus Schizothorax eurystomus and Triplophysa strauchii found to be the dominant species. Alburnus taeniatus was recorded for the first time in the ditches of Rishton. This species is listed in the Red Book of Uzbekistan.